(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The development of urban areas presents a significant challenge in providing affordable and high-quality housing. One innovative approach to addressing this issue is the implementation of the hybrid architecture concept, which integrates multiple functions and design elements within a single framework to create more flexible, multifunctional, and sustainable spaces. This study investigates the application of hybrid architectural principles in Rusunawa Jatinegara Barat, a vertical housing project in Jakarta intended for low-income communities. Employing a qualitative methodology, the research analyzes how the integration of public and private spaces, alongside commercial and residential components, can enhance residents’ quality of life while accommodating the increasing demands for urban space. Furthermore, this study utilizes Visual Graph Analysis (VGA) to examine the spatial and functional relationships within the Rusunawa design, thereby assessing the efficiency of circulation patterns and connectivity between spaces. The findings indicate that the application of hybrid architecture in Rusunawa Jatinegara Barat fosters the creation of inclusive, dynamic, and responsive environments that address both social and ecological needs, while also contributing positively to the sustainability of urban housing.